Emerging Trends and Challenges in Fog and Edge Computing for the Internet of Things - Bastien Confais; Benoît Parrein (IoT, 2022)
Current network architectures such as Cloud computing are not adapted to provide an acceptable Quality of Service (QoS) to the large number of tiny devices that compose the Internet of Things (IoT) [...]